2019
DOI: 10.1038/s41598-019-53832-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistome Biomarkers associated to the Pelagic Sediments of the Gulfs of Kathiawar Peninsula and Arabian Sea

Abstract: Antibiotic resistance has been one of the most persistent global issue. Specifically, marine microbiomes have served as complex reservoirs of antibiotic resistant genes. Molecular advancements have enabled exploration of the uncultured microbial portion from hitherto difficult to sample niches such as deeper oceans. The Gulfs of Kathiawar Peninsula have been known for their unique properties like extreme tidal variations, different sediment textures and physicochemical variations. Pelagic sediment cores across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
(46 reference statements)
2
6
0
Order By: Relevance
“…This is almost comparable to 17 gene families discovered at Tolo Harbour in the South China Sea [30]. The RA of all the genes varied according to the sampling location [50,60,61]. In the present study, the presence of ARGs was also recorded in sediments from sites S4 and S12 that were not in proximity to outfalls.…”
Section: Discussionsupporting
confidence: 85%
“…This is almost comparable to 17 gene families discovered at Tolo Harbour in the South China Sea [30]. The RA of all the genes varied according to the sampling location [50,60,61]. In the present study, the presence of ARGs was also recorded in sediments from sites S4 and S12 that were not in proximity to outfalls.…”
Section: Discussionsupporting
confidence: 85%
“…We believe their prevalence is due to the selective force imposed by the pharmaceuticals and antibiotics discharged into the ocean through wastewater streams [ 32 , 33 , 36 , 58 ]. Analogous findings were reported in polluted marine environments of the South China Sea [ 2 ], the Gulf of Kathiawar, and the Arabian Sea [ 18 , 19 , 58 ]. ARG abundances associated with mangrove sediments were predicted to be higher in Asian countries [ 19 ].…”
Section: Discussionsupporting
confidence: 83%
“…Next-generation sequencing has gained immense popularity since 2010 for comprehensively profiling microbial populations in polluted environments [ 57 ]. The high throughput sequencing approach employed in the present investigation successfully captured microbes from bacterial, archaeal, fungal, and viral domains [ 18 , 58 , 59 ]. This is the first study reporting the taxonomic profiles of all four microbial communities in the coastal sediments, suggesting the validity of shotgun sequencing in comprehensive biomonitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of microbial diversity and functions in the mentioned Gulfs have largely been focused on cultivation based approaches and very few molecular studies have been conducted on the shore sediments. Additionally, the presence of several on-shore industries like fertilizer, chemicals, oil refineries, power plants and ASSBRY (Alang Ship Breaking Yard) may have also influenced the deeper sediment microbiome leading to their variable gene profile 7 . Our previous insights into the pelagic sediment resistome profile by metagenomics approach have shown that the deeper sediments, earlier thought to be primeval are actually hosting microbes with a concerning number of resistance genes 7,8 .…”
mentioning
confidence: 99%